Topography and Mechanical Properties of Single Molecules of Type I Collagen Using Atomic Force Microscopy - Bozec, Laurent (Biophysical Society, 2005)
Although the mechanical behavior of tendon and bone has been studied for decades, there is still relatively little understanding of the molecular basis for their specific properties. Thus, despite consisting structurally of the same type I collagen, bones and tendons have evolved to fulfill quite different functions in living organisms. In an attempt to understand the links between the mechanical properties of these collageneous structures at the macro- and nanoscale, we studied trimeric type I tropocollagen molecules by atomic force microscopy, both topologically and by force spectroscopy. High-resolution imaging demonstrated a mean (± SD) contour length of (287 ± 35) nm and height of (0.21 ± 0.03) nm. Submolecular features, namely the coil-pitch of the molecule, were also observed, appearing as a repeat pattern along the length of the molecule, with a length of ∼8 nm that is comparable to the theoretical value. Using force spectroscopy, we established the stretching pattern of the molecule, where both the mechanical response of the molecule and pull-off peak are convoluted in a single feature. By interpreting this response with a wormlike chain model, we extracted the value of the effective contour length of the molecule at (202 ± 5) nm. This value was smaller than that given by direct measurement, suggesting that the entire molecule was not being stretched during the force measurements; this is likely to be related to the absence of covalent binding between probe, sample, and substrate in our experimental procedure.